Morpho-molecular analyses reveal a novel species of Phallus (Agaricales) from Hainan Province, China - Dong, Dan-Dan; Gao, Yu-Ting; Huang, Hai-Yan; Zheng, Guo-Wei; Zhao, Qi (Phytotaxa, 2026)
A novel species of the genus Phallus (Phallaceae, Agaricales), designated as Phallus hainanensis sp. nov., is described from tropical rainforests in Hainan Province, China. This new species is identified based on the integrative morpho-molecular evidence. Morphologically, it is characterized by an oval to ovoid egg in immature stage, a cylindrical, hollow, white to pale yellow pseudostipe, ellipsoid, smooth basidiospores, and a foul-smelling gleba. Microscopically, it possesses ellipsoid basidiospores measuring 4–5(–5.4) × 2–3 μm with smooth walls. Phylogenetic analyses based on the internal transcribed spacer (ITS) and nuclear large subunit (nuc-LSU) rDNA regions confirmed its distinct taxonomic position, forming a well-supported monophyletic clade sister to P. campanulatus. Sequence divergence between Phallus hainanensis and P. campanulatus is 5.7% (ITS) and 3.7% (nuc-LSU), respectively. A detailed description, illustrations, and phylogenetic affinities are provided. The new species enriches the diversity of Phallus in China, which currently comprises 29 known species, and contributes to fungal biodiversity.